2018
DOI: 10.1186/s13104-018-3738-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: the current status of carbapenem resistance in East Africa

Abstract: ObjectiveIn this systematic review, we present the molecular epidemiology and knowledge gaps of the carbapenem resistance in East Africa as well as the future probable research interventions that can be used to address the emergence of carbapenem resistance in the region.ResultsThe 17 articles which presented concrete information about the prevalence of carbapenem resistance in East Africa were reviewed. Tanzania exhibited the highest level of carbapenem resistance at 35% while DRC had the lowest level at 0.96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 47 publications
10
70
2
Order By: Relevance
“…Resistance to carbapenem which is the last resort was also recorded (MEM, 40%). Our findings therefore show an increase in carbapenem resistance in East Africa as compared to a systematic review done in the region that reported an incidence of 21% [14]. Tazobactam-Piperacillin the most used anti-Pseudomonal agent was effective to most isolates that were resistant to other antimicrobials Resistance to third generation β-lactams such as CAZ has been attributed to carriage of β-lactamases [15] bla NDM carriage was positive in only 10 from a total of 34 isolates that were resistant to Meropenem.…”
Section: Discussionsupporting
confidence: 55%
“…Resistance to carbapenem which is the last resort was also recorded (MEM, 40%). Our findings therefore show an increase in carbapenem resistance in East Africa as compared to a systematic review done in the region that reported an incidence of 21% [14]. Tazobactam-Piperacillin the most used anti-Pseudomonal agent was effective to most isolates that were resistant to other antimicrobials Resistance to third generation β-lactams such as CAZ has been attributed to carriage of β-lactamases [15] bla NDM carriage was positive in only 10 from a total of 34 isolates that were resistant to Meropenem.…”
Section: Discussionsupporting
confidence: 55%
“…Unlike a systematic review on ESBL-producing organisms in Africa [28], a high rate of ESBL-producing gramnegative bacteria was detected in this study (58.0% vs 22.8%). Nonetheless, carbapenem-resistance rate in A. baumannii, P. aeruginosa, and Enterobacteriaceae were lower than reported in other LMICs [29,30] and some high-income countries [31]. These patterns of antibiotic resistance in this setting could be explained by the high rate of use of third generation cephalosporins and a lack in exposure of admitted patients in this hospital to carbapenems [26].…”
Section: Discussionmentioning
confidence: 63%
“…Carbapenem‐resistant bacteria are a major public health threat all over the world (Centers for Disease Control & Prevention, 2013a, 2013b; Cuzon et al, 2011; Guh et al, 2015). However, little is still known about the distribution and characteristics of CRB outside health care or immediately related settings (Gupta et al, 2011; Kallen et al, 2010; Khuntayaporn et al, 2012; Rhomberg & Jones, 2009; Ssekatawa et al, 2018). This gap in knowledge is especially significant in the United States, where only three specific studies about the prevalence of CRB in the environment, all three in freshwater, have been performed (Ash et al, 2002; Aubron et al, 2005; Harmon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because the use of carbapenems is restricted to healthcare facilities (Bradley et al, 1999; Paterson, 2000), most studies on isolating and characterizing CRB have also focused on these and immediately related settings (Gupta, Limbago, Patel, & Kallen, 2011; Kallen, Hidron, Patel, & Srinivasan, 2010; Khuntayaporn, Montakantikul, Mootsikapun, Thamlikitkul, & Chomnawang, 2012; Rhomberg & Jones, 2009; Ssekatawa, Byarugaba, Wampande, & Ejobi, 2018). However, other β‐lactams including extended‐spectrum penicillins and cephalosporins are used to treat patients outside healthcare facilities and are used in agriculture as well.…”
Section: Introductionmentioning
confidence: 99%